A Planning Framework Foregrounding Equity in Mathematics Teaching and Learning. (3rd April 2023) - Jackson, Christa; Buchheister, Kelley Woolford; Taylor, Cynthia E.
ABSTRACT: Lesson planning is a crucial component of effective mathematics instruction. However, existing lesson planning frameworks and design models do not explicitly foreground equity and inclusion within instructional planning which are necessary in teaching every student. The What-How-Who structure frames the planning process by foregrounding who the learners are so teachers can situate differentiated mathematical learning experiences in ways that foster each student's construction of knowledge. In this article, we conceptualize the What-How-Who planning structure, which mathematics educators at any age or grade level can use as a lens to incorporate equity-based practices as they design lessons and activities.